The Storage related changes in short-set cream cheese manufactured using thermophilic starter culture and direct acidification technique - Soumitra Hazra, JM Mallik, AM Patel, AJ Gokhale and AI Shaikh (Indian Journal of Dairy Science, 2023)
Cream cheese is a fresh acid curd variety with semi-soft body, manufactured by the gradual, quiescent acid gelation of milk. The typical flavour profile of cream cheese is cultured diacetyl with little bit lactic acid flavour as well as aroma. It is envisaged that demand of cream cheese will increase in upcoming years due to its application as spread and it having higher nutritional value compared to similar products available in the market. The purpose of the study was to observe changes in sensory, physicochemical and microbial quality during storage in short-set cream cheese samples manufactured by using thermophilic starter culture and direct acidification technique and was compared with control cream cheese manufactured using mesophilic starter culture. All the three samples i.e., control cream cheese made using mesophilic culture (MC), cream cheese made using thermophilic culture (TC) and cream cheese made using laboratory grade lactic acid (SLA) were stored in re-closable polypropylene tubs at 7 ± 2°C. During storage study, flavour score, FFA, tyrosine value was significantly affected by storage period (P), treatment (T) and the interaction of T × P. Moisture, pH, titratable acidity, sensory parameters (except flavour) were significantly affected by storage period (P) and treatment (T). The flavour scores were also significantly affected by storage period (P), treatment (T) as well as the interaction of T × P. All the three samples had storage stability up to 15 days at 7 ± 2°C.